Peran Gen Z dalam Melestarikan Budaya Islam Lokal di Era Digital - Kusumaningtyas, Sinta (Journal of Islamic Communication Studies, 2025)
This study examines the role of Generation Z in preserving local Islamic culture in the digital era and aims to understand their contributions to sustaining such cultural practices. Employing a qualitative-descriptive approach, the research utilizes in-depth interviews with six informants aged 20–21 years. The findings indicate that globalization and technological advancement influence the ways in which Generation Z understands and engages in cultural preservation, while social media provides new spaces for cultural revitalization through creative and collaborative content. Drawing on Robertson’s (1995) theory of glocalization, this study explains Generation Z’s capacity to integrate local identity into global trends. The results demonstrate that they function both as cultural heirs and innovators, maintaining the relevance of tradition through digital creativity, value adaptation, and the production of cultural content within digital spaces.